CORROSION of BOILER TUBES in SOUTH BAGHDAD ELECTRIC STATION - Kh. Haweel, Cecilia; Lazar, Janet (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
The corrosion of low carbon steel boiler tubes in demi water had been investigated. The purpose of this investigation was to determine the change produced in corrosion behavior of the carbon steel as a result of the specific presence of chloride and copper ions in the water under different temperatures. For low carbon steel experiments, the temperature was taken in three levels (125, 175, and 215°C) under about 27 bar pressure and 1500 rpm in autoclave. Using weight loss technique, the corrosion rate ranges from (85 to 789 gmd) for low carbon steel boiler tubes.